2020
DOI: 10.1177/1010539519899777
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Electronic Cigarette Use and Levels of High-Sensitivity C-Reactive Protein and Uric Acid

Abstract: The present study investigated whether electronic cigarette use, which is becoming increasingly common, was related to systemic inflammation that may lead to cardiovascular disease, similar to conventional cigarette smoking. The study included 1208 men (19-65 years old) who participated in the 7th Korean National Health and Nutrition Examination Survey (2016). The participants were categorized as electronic cigarette users, conventional cigarette users, and nonsmokers. Serum high-sensitivity C-reactive protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Our findings from bivariate analyses are consistent with, and seemingly build upon, reports of independent associations between e-cigarette use and depression, and depression and elevated CRP [4,5,12,37,38], and a lack of evidence for a significant association between elevated CRP and e-cigarette use [42,43]. Similar to previous studies, we found that fewer women use e-cigarettes, yet are at elevated risk for depression (50%) and serum CRP ≥ 8.0 mg/L (100%) compared to men (Table 2) [38,[44][45][46][47].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings from bivariate analyses are consistent with, and seemingly build upon, reports of independent associations between e-cigarette use and depression, and depression and elevated CRP [4,5,12,37,38], and a lack of evidence for a significant association between elevated CRP and e-cigarette use [42,43]. Similar to previous studies, we found that fewer women use e-cigarettes, yet are at elevated risk for depression (50%) and serum CRP ≥ 8.0 mg/L (100%) compared to men (Table 2) [38,[44][45][46][47].…”
Section: Discussionsupporting
confidence: 89%
“…It is well accepted that smokers are more likely to experience depression compared to non-smokers [ 35 , 36 ], and a number of studies have found that e-cigarette users also are at greater risk for depression [ 4 , 5 , 6 , 37 ]. Separately, both vaping and depression have been independently associated with increased inflammation [ 11 , 12 , 38 ]. Using data from a nationally representative sample of the U.S. population, we have found evidence consistent with early findings of current e-cigarette use being associated with increased likelihood of depression, and evidence of inflammation being associated with depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, a cross-sectional study in Korea reported that cigarette and e-cigarette use was associated with increased uric acid [10], [28]. The suggested mechanism was that the use of e-cigarettes causes systemic inflammation characterized by an increase in hs-CRP, which contributes to an increase in uric acid levels and a higher risk of hyperuricemia [28]. A Brazilian study also revealed that smokers experienced increased levels of hs-CRP than non-smokers, and smokers with metabolic syndrome had high hs-CRP levels twice [8].…”
Section: Discussionmentioning
confidence: 72%
“…The use of cigarettes and e-cigarettes also seems to increase uric acid. In accordance, a cross-sectional study in Korea reported that cigarette and e-cigarette use was associated with increased uric acid [10], [28]. The suggested mechanism was that the use of e-cigarettes causes systemic inflammation characterized by an increase in hs-CRP, which contributes to an increase in uric acid levels and a higher risk of hyperuricemia [28].…”
Section: Discussionmentioning
confidence: 87%